An evaluation of time in establishing operation on the effectiveness of functional communication training. Issue 1 (25th November 2014) - Derosa, Nicole M.; Fisher, Wayne W.; Steege, Mark W.
<x xml:space="preserve">Abstract</x> We examined whether different durations of exposure to relevant establishing operations (EO) during treatment of problem behavior affected treatment efficacy and response bursting. In Study 1, we compared 2 functional communication training (FCT) interventions. In the first treatment, we used a card touch as the target mand; this was associated with limited exposure to the EO because we could physically guide the mand at prescribed times. In the other treatment, we used a vocal response as the mand; this was associated with longer exposure to the EO because it was not possible to guide the response. In Study 2, we exposed participants to time‐based reinforcement schedules that were yoked to the schedules of obtained reinforcement from the 2 FCT interventions in Study 1. Results indicated that limited exposure to the EO was associated with less response bursting, larger and more rapid reductions in problem behavior, and faster acquisition of the alternative mand.